Pemahaman Dasar untuk Pengimplementasian Manajemen Sumber Daya Manusia dalam Organisasi Non-Profit - Pratiwi, Apriyani; Arnu, Anggi Pasca (Peneliti.net, 2025)
This research discusses the basic understanding needed to implement human resource management (HRM) in the context of non-profit organizations. Research focus includes basic HRM concepts, specific challenges faced by non-profit organizations, and strategies to ensure successful HRM implementation. By analyzing these aspects, this research aims to provide in-depth insight into how non-profit organizations can effectively manage and optimize the potential of their human resources.